Pengaruh Faktor Keamanan, Lingkungan, dan Aturan terhadap Harga Sewa Kos Di Yogyakarta: The Influence of Safety, Environmental, and Regulatory Factors on Boarding Rental Prices in Yogyakarta - Fadia Afra Nazaha; Vanya Amalia; Devania Riska Putri; Vella Violita (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2024)
The objective of this writing is to analyze the factors of price, safety, environment, and regulations in renting boarding houses. The data used in this writing employs a quantitative research method obtained from respondents through survey questionnaires. It is analyzed using the multiple linear regression method, which concludes that one of the profitable property investments is in boarding house properties. Based on the results of research and discussion, it show that the environment is significant to the price of boarding house rentals. Meanwhile, security and regulations are not significant to the price of boarding house rentals. Boarding house owners can easily and conveniently promote their properties, while tenants gather information through direct surveys (visiting) the selected boarding houses. Before choosing a boarding house to live in, it is advisable to consider factors such as safety, environment, and rental prices. These are the considerations before deciding which boarding house to choose. It is recommended to always choose a boarding house by paying attention to a comfortable environment, meeting safety standards, and appropriate rental prices